PRMT1 promotes immune escape in hepatocellular carcinoma by regulating arginine methylation modification of MYC protein - Han Zhou; Yang Wang; Dan Wang; Mei Zhang; Kaidi Wang; Chunhui Liu (Epigenetics)
Arginine methyltransferase 1 (PRMT1) is widely recognized as an oncogene in various cancers. However, its specific role and underlying mechanisms in hepatocellular carcinoma (HCC) remain insufficiently understood. This study investigated the function of PRMT1 in HCC development and immune evasion. A comprehensive approach combining database analysis (including TCGA, The Human Protein Atlas, Kaplan-Meier Plotter, and TIMER2.0), molecular techniques (such as RT-qPCR, Western blot analysis, and co-immunoprecipitation), cell-based assays (including MTT, colony formation, transwell, and T cell killing assays), and in vivo models was employed to explore PRMT1’s role in HCC. The findings revealed a marked upregulation of PRMT1 in both HCC clinical samples and cell lines. Depletion of PRMT1 inhibited cell proliferation and immune evasion while reducing cell migration and invasion. Mechanistically, PRMT1 was shown to interact with MYC, facilitating its arginine methylation and enhancing its protein stability. Moreover, re-expression of MYC significantly reversed the anti-tumour effects associated with PRMT1 depletion. In vivo experiments further corroborated these results. Collectively, PRMT1 promotes HCC progression and immune escape by mediating ADMA methylation of MYC, thereby regulating its stability and expression.